2018
DOI: 10.1128/aem.00551-18
|View full text |Cite
|
Sign up to set email alerts
|

Survival of the Enveloped Virus Phi6 in Droplets as a Function of Relative Humidity, Absolute Humidity, and Temperature

Abstract: Infectious diseases caused by enveloped viruses, such as influenza, severe acute respiratory syndrome (SARS), and Middle East respiratory syndrome (MERS), cause thousands of deaths and billions of dollars of economic losses per year. Studies have found a relationship among temperature, humidity, and influenza virus incidence, transmission, or survival; however, there are contradictory claims about whether absolute humidity (AH) or relative humidity (RH) is most important in mediating virus infectivity. Using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
219
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(245 citation statements)
references
References 49 publications
24
219
2
Order By: Relevance
“…These results are in agreement with other studies that suggested that the aerosol spread of the influenza virus is both dependent upon relative humidity and temperature, although performed in animal models 14 , and that the virus survival in droplets is higher at high humidity levels with a significant decrease on its infectivity rate at mid-levels of humidity 15 . Additionally, other authors suggest that some diseases spread faster in high humidity levels 16 , reporting an odds ratio for a community-acquired pneumonia case, diagnosed with leggionaire's disease a , 3.1 times higher in high humidity level (above 80%) than when submitted to humidity levels below 50%, at temperatures of 16-27 ºC (60º-80ºF).…”
Section: Resultssupporting
confidence: 93%
“…These results are in agreement with other studies that suggested that the aerosol spread of the influenza virus is both dependent upon relative humidity and temperature, although performed in animal models 14 , and that the virus survival in droplets is higher at high humidity levels with a significant decrease on its infectivity rate at mid-levels of humidity 15 . Additionally, other authors suggest that some diseases spread faster in high humidity levels 16 , reporting an odds ratio for a community-acquired pneumonia case, diagnosed with leggionaire's disease a , 3.1 times higher in high humidity level (above 80%) than when submitted to humidity levels below 50%, at temperatures of 16-27 ºC (60º-80ºF).…”
Section: Resultssupporting
confidence: 93%
“…3. This is similar to previous reports where MERS-CoV cases increased with low humidity [9,[11][12][13]. Our findings may clarify viral seasonality, as it explains why most MERS-CoV outbreaks occurred between April and August, where temperatures reached the highest and humidity reached the lowest [14].…”
Section: Discussionsupporting
confidence: 91%
“…The strength of this study is the large number of MERS-CoV patients included in the analysis, and the study identifies important factors affecting MERS-CoV viral seasonality. In agreement with previous reports [11,13], the study highlights the need for considering climate factors on MERS-CoV guidelines for control measures and prevention. The overall findings of the study are that the higher the temperature and ultraviolet index, the higher incidence of MERS-CoV infections, and vice versa for humidity and wind speed.…”
Section: Discussionsupporting
confidence: 91%
“…Utilizing an established guinea pig model of transmission, Lowen et al demonstrated that low RH (20%‐30%) is optimal for influenza virus transmission . Prussin et al also demonstrated the same influence of low RH on infectivity using bacteriophages . Testing bioaerosol samplers under a range of IAV transmission conditions is essential for determining the usefulness of these sampling devices.…”
Section: Discussionmentioning
confidence: 99%